2020
DOI: 10.1002/ejhf.1755
|View full text |Cite
|
Sign up to set email alerts
|

One‐year mortality after implantable cardioverter‐defibrillator placement within the Veterans Affairs Health System

Abstract: Aims Implantable cardioverter‐defibrillator (ICD) therapy reduces mortality in patients with heart failure and current guidelines advise implantation of ICDs in patients with a life expectancy of >1 year. We examined trends in all‐cause mortality in patients who underwent primary or secondary prevention ICD placement in the Veterans Affairs (VA) Health System. Methods and results US veterans receiving a new ICD placement for primary or secondary prevention of sudden cardiac death between January 2007 and Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 24 publications
0
18
0
8
Order By: Relevance
“… 60 , 61 Furthermore, hospitalization and early mortality remain common in the ICD population despite technical improvements and implementation of telemonitoring. 3 , 4 , 62 This review has demonstrated that low PA following device implantation and a decline in PA are both associated with ICD therapy, HF hospitalization, and mortality. Hence, PA as a surrogate for functional capacity could reflect worsening of functional status and be a marker of an increased risk of clinical events and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 60 , 61 Furthermore, hospitalization and early mortality remain common in the ICD population despite technical improvements and implementation of telemonitoring. 3 , 4 , 62 This review has demonstrated that low PA following device implantation and a decline in PA are both associated with ICD therapy, HF hospitalization, and mortality. Hence, PA as a surrogate for functional capacity could reflect worsening of functional status and be a marker of an increased risk of clinical events and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, ICD carriers are at risk of frequent hospital readmission after implantation, increased mortality rates, and psychological distress due to appropriate and inappropriate ICD shocks. 2 , 3 , 4 , 5 , 6 , 7 , 8 The role of physical behavior (PB) is investigated in an attempt to find new predictors and markers of clinical deterioration. Contrary to physical activity (PA), which focuses only on body movement that requires energy expenditure, PB is an umbrella term for an individual’s behavior and activities throughout day and night, which also includes sleep, daily activities, posture, rest-activity patterns, and sedentary behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Fudim et al 10 . noted that 1‐year mortality after ICD implantation, for primary or secondary prevention, increased with increasing age reaching an incidence of 32% in the oldest patients (median age 82 years).…”
Section: Treatment Of Ischaemic Heart Failurementioning
confidence: 99%
“…There remains, then, an important need to refine both arrhythmic and competing mortality assessment in secondary prevention patients. Indeed, as a recent analysis of ICD recipients in the Veterans Administration System demonstrated, 65 1-year mortality was 33.3% in those greater than 80 years of age, emphasizing the important considerations of integrating and refining our assessment of competing risk in this population.…”
Section: Systems Of Care For Secondary Prevention Patients and Opportunities For The Futurementioning
confidence: 99%